Partisipasi Followers Melalui Like pada Konten Informasi Akun Instagram @Bogor24update dalam Membentuk Citra Media Sosial - Levinda Melati; Muhammad Luthfie; Agustini Agustini (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humani..., 2026)
This study aims to analyze followers' participation through the like feature on disaster information content of the Instagram account @bogor24update and its contribution to shaping social media image. A qualitative approach with a single case study method was employed. Data were collected through in-depth interviews and documentation, including insight data and screenshots of posts from December 2025 to January 2026. The findings reveal that likes represent the most dominant form of initial participation. Likes are not merely interpreted as expressions of enjoyment but rather as indicators of attention, information acceptance, and forms of empathy and social concern toward disasters. The high number of likes is influenced by the urgency of the event, its widespread impact on the community, and the quality of visual content. Participation through likes also contributes to building @bogor24update's image as a relevant, fast, and trustworthy local information medium on social media. However, establishing a strong image also requires active two-way communication between the admin and followers. This study recommends improving visual content quality and admin responsiveness to the audience.